(untitled) (Nordic Journal of African Studies, 2002)
This paper argues the case for more educational publications in Swahili as a good medium educational and national development. It acknowledges that education is not only a capital investment in the development of human resources but it also immensely contributes to the development of a nation. However, educational development cannot be achieved without support services such as books in all fields and in a language that is readily understood by many people. This paper shows that Swahili, the national and co-official language of Kenya, can play an important role in the production of educational publications. It explores the extent of publishing in Swahili and other African languages for various educational levels in Kenya, namely children’s books, school textbooks, tertiary level, special education, adult education and fiction. While appreciating that there exist few publications in Swahili, this paper argues that Kenya stands to gain a lot if she assigns Swahili a larger role, but it at the same time cautions against downplaying the international significance of English.